2019
DOI: 10.1200/jco.2019.37.7_suppl.589
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tumor mutational burden (TMB), PD-L1, and DNA repair genes to assess correlation with immune checkpoint inhibitors (ICIs) response in metastatic renal cell carcinoma (mRCC).

Abstract: 589 Background: ICIs have revolutionized treatment for mRCC; however there are limited predictive biomarkers for response to ICIs. PD-L1 status is still controversial demonstrating little predictive utility in mRCC. TMB is predictive for response to ICIs in melanoma and non-small cell lung cancer (NSCLC), but has not been validated in mRCC. Here, we assess the correlations between TMB and PD-L1 status with outcomes to ICI treatment in mRCC. Methods: 34 patients (pts) with mRCC who had previously received ICI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Special attention should be given to mRCC because no positive correlation between tumor mutational burden and ICI response was observed in this tumor type. In a small cohort of 34 patients, Labriola et al [36] showed that neither tumor mutational burden nor PD-L1 expression was correlated with patient outcomes or with ICI response [36] . Interestingly, Turajlic et al [37] showed that ccRCC tumors harbour the highest rate of insertion-deletion (indels) DNA alterations, leading to one of the highest neoantigenicity potential.…”
Section: Insufficient Tumor Antigenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Special attention should be given to mRCC because no positive correlation between tumor mutational burden and ICI response was observed in this tumor type. In a small cohort of 34 patients, Labriola et al [36] showed that neither tumor mutational burden nor PD-L1 expression was correlated with patient outcomes or with ICI response [36] . Interestingly, Turajlic et al [37] showed that ccRCC tumors harbour the highest rate of insertion-deletion (indels) DNA alterations, leading to one of the highest neoantigenicity potential.…”
Section: Insufficient Tumor Antigenicitymentioning
confidence: 99%
“…In a small cohort of 34 patients, Labriola et al . [ 36 ] showed that neither tumor mutational burden nor PD-L1 expression was correlated with patient outcomes or with ICI response [ 36 ] . Interestingly, Turajlic et al .…”
Section: Mechanisms Of Primary and Secondary Resistance To Icimentioning
confidence: 99%
“…This may be related to the higher quality of antigens in these tumor types, resulting from viral antigens (in MCC), a high number of indel mutations (in RCC), and complex chromosomal rearrangements (in mesothelioma). TMB also has poor predictive value within some tumor types such as gliomas and renal cell cancers (25). Concerning clear cell renal cancer, Swanton's group showed that TMB is not a biomarker of efficacy of ICI therapy.…”
Section: B Tmb As a Potential Biomarker Of Ici Responsementioning
confidence: 99%